Effect of Soil Preparation Depth on Nutrient Leaching and Nutrient Uptake by Young Vitis vinifera L. cv. Pinot noir - Conradie, W.J.; Van Zyl, J.L.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
The effect of soil preparation depth on leaching of N, Ca, Mg and K was determined for a granitic soil by means of field Iysimeters. For this purpose trenches (22,5 m x 2,7 m) with depths of 400 mm (T40), SOO mm (TSO) and 1200 mm (T120) were excavated, lined with plastic sheets and fitted with drainage pipes. After refilling the soil in the original sequence each Iysimeter was planted with fifteen Pinot noir vines grafted onto 99 Richter, two years after soil preparation. The experimental site was situated on a 15 degree slope and drained naturally. Leachates were collected quantitatively and analysed. Nutrient uptakes of vines were determined up to the end of the third growing season. Soil loosening stimulated the mineralisation of organic material, resulting in leaching of nitrates. Higher amounts were leached from the deeper treatments and losses declined over time. Results indicated that soil-derived N can supply the N requirement of grapevines for the first three years after soil preparation. Leaching losses of Ca, Mg and K pointed to a steady state being attained four to five years after soil preparation. Once this state had been attained, annual Ca losses were approximateir 200 kg.ha·’, irrespec ive of soil preparation depth. Magnesium losses correl1ated with preparation depth, ranging from 20 kg.ha for T40 to 70 kg.ha for T120. Potassium losses rarely exceeded 20 kg.ha , thus not necessitating any major adjustments in fertilisation programmes. Soil preparation depth had a significant effect on the development of the young vines. Full bearing stage was reached at the end of the second season for T120 and the end of the third season for TSO and T40. During the second growing season foliar nitrogen uptake amounted to 12,6 kg.ha·’, 15,2 kg.ha·’ and 24,5 kg.ha·’ for T40, TSO and T120, respectively. In the third season N uptake on T120 (52,5 kg.ha-’) was comparable to that of mature vines while TSO (37,2 kg.ha-’) and T40 (31,5 kg.ha-’) required considerably less N. During the non-bearing stage the Ca uptake was comparable to that of N and 60% higher than that of K. When the first grapes were harvested (third season), K uptake surpassed that of Ca for T40 and TSO. Magnesium uptake never exceeded 15 kg.ha·’, irrespective of soil depth.